Global implications of capital account liberalisation in China - Sun, Yang (2017)
This paper studies the determinants of foreign direct and portfolio investment flows and projects China’s balance of payments and international investment positions from 2016 to 2025. By conducting dynamic panel regressions on 24 sample countries for two periods 1997-2009 and 2003-2015, we provide empirical evidence for structural shift in global capital markets. Our projections for China’s international investment positions are based on the assumption that China’s capital account liberalisation would be largely achieved by the end of 2025. Based on the regression model, the projections show that China’s foreign direct investment assets will gradually catch up with foreign direct investment liabilities and exceed the latter by 2025. Meanwhile, China’s foreign portfolio investment assets and liabilities will accumulate at a similar pace with negative net foreign portfolio investment position over the next decade. Moreover, official foreign reserves of China will grow in value but decline as a share of GDP. Overall, China will continue to be a net creditor, but the current account as a share of GDP will decrease over time.